1、(1-1÷2^2)(1-1÷3^2)(1-1÷4^2)...(1-1÷10^2)
=(1-1/2)*(1+1/2)*(1-1/3)*(1+1/3)*…*(1-1/10)*(1+1/10)
=(1/2)*(3/2)*(2/3)*(4/3)*(3/4)*…*(9/10)*(11/10)
=(1/2)*(11/10)
=11/20
2、1^2-2^2+3^2-4^2+...+99^2-100^2
=(1-2)*(1+2)+(3-4)*(3+4)+……+(99-100)*(99+100)
=-(1+2)-(3+4)-……-(99+100)
=-(1+2+3+4+……+99+100)
=-5050
3、(2+1)(2^2+1)(2^4+1)(2^8+1)...(2^64+1)-2006
=(2-1)(2+1)(2^2+1)(2^4+1)(2^8+1)...(2^64+1)-2006
=(2^2-1)(2^2+1)(2^4+1)(2^8+1)...(2^64+1)-2006
……
=(2^128-1)-2006
=2^128-2007
2^n的个位数字依次为2、4、8、6的循环,所以2^128的个位数字为6
那么2^128-2007的个位数字为9即原式的个位数字为9